Ausencia de síntesis de trehalosa en Acidithiobacillus ferrooxidans ATCC 23270 y Acidithiobacillus ferrivorans CF27 a baja temperatura - Castañeda-Fernandez , Maria (2023)
Trehalose is a type of carbohydrate that protects against different types of stress and is also used as a source of carbon storage in prokaryotes. There are four different ways of synthesizing trehalose in Acidithiobacillus ferrivorans and two in Acidithiobacillus ferrooxidans, but its purpose remains unknown. This study aimed to measure the production of trehalose under different conditions by quantifying it in three culture media at two different temperatures. The growth kinetics of both species were also assessed, and the trehalose concentration was analysed during the early stationary phase using an enzymatic method. The results showed that the modified 9K medium with ferrous iron at 28°C had the highest production of trehalose, with A. ferrivorans CF27 having a higher production of 0.34 µmol/mg protein compared to A. ferrooxidans ATCC 23270 at 0.31 µmol/mg protein. When using CuS, the production of trehalose was lower, with 0.02 and 0.03 µmol/mg protein for A. ferrivorans CF27 and A. ferrooxidans ATCC 23270, respectively, while no trehalose was detected in the presence of zinc. At 15°C, the enzymatic method did not detect any trehalose in all three culture media, this would indicate that this carbohydrate does not protect against low temperatures in either species.